2020
DOI: 10.3390/molecules25020359
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Trace Elements in Selected Locations of the Human Brain in Individuals with Alcohol Use Disorder

Abstract: Trace element distribution varies in different locations of the human brain. Several elements were found to cause various negative effects, such as neurodegeneration. In this paper, we analyzed the interactions between seven trace elements: zinc (Zn), selenium (Se), manganese (Mg), iron (Fe), copper (Cu), chromium (Cr) and cobalt (Co) in individuals with alcohol use disorder (AUD) and individuals without (control group). Brain tissue samples from 31 individuals with AUD and 31 control subjects were harvested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Currently, it is believed that the toxic effects of alcohol on organs are mainly associated with the activity of alcohol metabolites, induction of oxidative stress, and translocation of intestinal endotoxins into the bloodstream [ 17 , 18 , 19 , 20 ]. These processes lead to cell damage and stimulation of inflammatory reactions releasing a large number of cytokines, among others such as TNF-alpha and IL-6 [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is believed that the toxic effects of alcohol on organs are mainly associated with the activity of alcohol metabolites, induction of oxidative stress, and translocation of intestinal endotoxins into the bloodstream [ 17 , 18 , 19 , 20 ]. These processes lead to cell damage and stimulation of inflammatory reactions releasing a large number of cytokines, among others such as TNF-alpha and IL-6 [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The onset of psychiatric conditions or exaggerations of their symptoms might be induced by numerous factors including genetic predispositions, infections, inflammations, trace elements and vitamin levels, severe stress, postpartum complications, intellectual disability, neurodegenerative diseases, trauma, stimulants, and socio-economic and psychological factors [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The importance of various trace elements’ concentrations in human organisms cannot be underestimated since they are a crucial factor responsible for either induction or exaggeration of numerous disease symptoms ( Table 1 ) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although these correlations have not reached statistical significance, they shed new light on the complex processes of homeostasis in trace element metabolism. So far, such intercorrelations have been tracked by our team in body fluids such as fluid from the anterior chamber of the human eye [ 42 , 43 ], and in tissues collected post mortem from various sites of the human brain [ 12 , 13 , 44 , 45 ]. Our research to date has confirmed that in the case of disturbance of physiological processes that take place in eye diseases (cataracts), AUD, or are the result of medical procedures such as hemodialysis [ 44 ], there are visible changes in the intercorrelation matrices.…”
Section: Discussionmentioning
confidence: 99%
“…For calibration, we used ICP commercial analytical standards (Romil, Cambridge, UK). The conditions of measurements and validation parameters were described previously [ 12 ]. The uncertainty for the whole analytical process was at the level of 20%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation